Diversity of Ornamental Fishes in Lalitpur, Nepal - Dhungana, Bipina; Thakur, Babita Kashyap (Patan Prospective Journal, 2025)
Lagankhel, Patan, Satdobato and Jawalakhel of Lalitpur. The objectives of this report were to list and compare the diversity of ornamental fishes with the comparison of the abundance of ornamental fishes. Field survey was conducted for four months. The questionnaire method was done within nine shops. The data were analysed in Microsoft Excel, focusing on the Shannon index, Evenness and Species Richness of ornamental fishes in local shops of Lalitpur. This survey shows that a total of 1581 individual ornamental fish species were recorded belonging to eight different families and 21 species, where 19 of them were exotic where species like Carassius auratus, Gymnocorymbus ternetzi, Poecilia reticulata, and Pterophyllum scalare are dominating. Where Amphilophus hybrid is the least dominanting with only five in number. Which are imported mainly from India and Thailand. Only two Puntius conchonius and Danio rerio were found native to Nepal in Lalitpur. The calculated Shannon Diversity index (H′) 2.65309, Evenness (J) 0.8418 and Species Richness of 21 shows that a moderately high biodiversity of ornamental fishes in the market of Lalitpur that has a stable, diverse and well-stocked community of ornamental fish in Lalitpur. In conclusion, this study provides meaningful analysis of diversity of ornamental fish in Lalitpur. Also shows that despite the dominance of exotic fish species, native species remains underutilized, showing an opportunity for sustainable, indigenous alternatives. A viable shift for cultivating native ornamental fish species could reduce dependency on imports and enhance local aquaculture in Nepal, minimizing the risk driven by exotic fish species arising from aquarium trade.